Personal router using LINUX - Amilia Yanti, Abdullah (2005)
The useful of network today are a famous thing in organization.There are many types of network such as local area network and metropolitan area network.All types of networks need a suitable device that allows the communication between the networks.The muter is a suitable device for this job.The router is a computer device that allows more than one network to communicate each other.The router also functions to detect the corrupted packet that happened in the connection among the network through the router.For the small organization, the cost to have the own router is a high cost. So this project aim is to help the small organization to build the personal router.The personal router is making using the personal computer that can be function as a router.For this time, this project implement to the Intranet condition where the two computers connected each other with the personal computer as a router.The two computers has been configure with two different LAN.The software are develop base on Linux environment and use QT Designer as a platform.The language for the software coding use a C and C++ language.The detail of this project was included in this report.